TIE-MAC: tolerable interference estimation-based concurrent medium access control for WLAN mesh networks. (2015) - Lei, Lei; Cai, Shengsuo; Zhou, Liang; Chen, Xiaoming; Feng, Xinxin
This paper proposes TIE-MAC, tolerable interference estimation-based concurrent medium access control protocol for wireless local area network (WLAN) mesh networks. The goal is to increase spatial reuse, achieve high throughput and reduce average energy consumption through exploiting concurrent transmissions among neighbouring nodes. TIE-MAC confirms that the tolerable interference of the receiver plays a key role in determining the efficiency of concurrent transmission scheduling, and puts forward a novel tolerable interference estimation mechanism, enabling the receivers to precisely estimate their tolerable interference. Meanwhile, a concurrent transmission gap (CTG) is inserted between the transmission of the RTS/CTS and data packets to offer the nodes in the vicinity of the receiver the chance to schedule possible overlapping transmissions. The size of the CTG is optimised using an exponential smoothing model-based adjustment algorithm. Moreover, sequenced acknowledgements (ACKs) are introduced in TIE-MAC and used in combination with the tolerable interference estimation mechanism to avoid possible collisions among different concurrent transmissions. Simulation results show that TIE-MAC gains better throughput and energy consumption performance in comparison with existing concurrent transmission protocols as well as the active WLAN mesh standard.